Ukrainian Pedagogical Press as a Source of Representation of Innovative Pedagogical Ideas (1991-2013) - Liliya Wajda (Pedagogical Discourse, 2013)
The article analyzes the Ukrainian pedagogical press as a source of representation of innovative pedagogical ideas in Ukraine since 1991. It was found that the publications in the pedagogical press recreate the process of accumulation of knowledge and the development of pedagogy related to educational practice, make it possible to trace the influence of this process on the ideas and views of national researchers and practitioners, reveal its patterns and differences, reflect the interaction with the environment - specific political and socio-economic circumstances. It is proved that both the historical and pedagogical periodicals source materials provide a variety of educational topics, which encompasses all the complexity and achievement of pedagogical research. It is periodical press that has played a significant role in the development of innovative pedagogical ideas in the period under research: in its pages an extensive, often contradictory, process of forming, grinding, critical exploration and  understanding of  pedagogical ideas took place.